Peningkatan Keterampilan Bahasa Inggris melalui Permainan Bingo di Thamkhiri Wittaya School, Thailand - Damrah, Selena Suardi; Lubis, Deni; Anggini, Karlita (Jurnal Pusat Inovasi Masyarakat, 2024)
The era of globalization is characterized by interactions between languages and cultures. This condition requires countries in the world to master foreign languages, especially English. Thailand is one of the countries that strives to improve English language skills through educational curriculum development, especially in secondary schools such as Thamkhiri Wittaya School. This activity also aims to evaluate the effectiveness of Bingo games in improving student's English skills at Thamkhiri Wittaya School. The program was part of IPB University's Community Service Program (KKN) involving students from grade 2-6 at Thamkhiri Wittaya School. The program runs from Sunday to Thursday, at 11:00 am to 4:00 pm. The results showed that the interactive learning method through Bingo game was effective in improving student’s English skills at Thamkhiri Wittaya School, but there were challenges in increasing students' learning motivation and lack of variety in learning activities.